FUNGSI MANAJEMEN DALAM PENGEMASAN PRODUK BERBASIS TEKNOLOGI INFORMASI DI UNIT PELAKSANA TEKNIS (UPT) PERPUSTAKAAN UNIVERSITAS RIAU - HELMI, YUHELMI (Human Sustainability Procedia, 2018)
This study aims to determine the process of planning, organizing, implementation, and evaluation in the packaging of information technology-based products that have been run in UPT Library University of Riau and the constraints faced when packaging IT-based products are implemented. The type of research used is descriptive evaluative type, ie to an already running program (Ex Post Program Evaluation). Respondents in this research are 3 staffs involved in planning process, organizing, implementing and evaluating product based on information technology and 3 person of leadership as reinforcement result of this research. It must be aware of its strengths and weaknesses, which then think and plan what needs to be done for further improvement. The results showed that Planning, organizing and implementation and evaluation in packaging of products based on Information Technology in UPT Library University of Riau has not been fully implemented well this is due to technical constraints. Keyword: Function Management, Packaging Products, based on information technology, UPT library University of Riau